Role of Technology in Education - SHARMA, DR. MEENAKSHI (The journal of contemporary issues in business and government, 2021)
With the advancement in technology there is a rapid change in the manner in which individuals live, associate, impart, and lead business. This change is regularly alluded to as the "digital revolution," which is the headway of innovation from simple, electronic and mechanical apparatuses to the technically advanced instruments accessible today. The utilization of digitalization in the learning procedure and training rehearses in formal instructing is exceptionally subjected to the capacity of educators to deliver it without imperiling the lavishness of the study hall condition, to be specific the consideration that understudies need to follow the progression of argumentation and to ensure the nature of the inquisitive. In this paper, a research is made on the impact of technology in the modern era and how it impact the life of the scholars, graduates and alike as yet more advancements have to be done in the implementation of digital technology in the study hall and on the performance of the educator particularly on how performing various tasks influences the educator job in-class in delivering and explaining the content in a more precise manner that is easy for the students to grab things more easily.